120 MeV Au+9 swift heavy ion irradiation of pulsed laser deposited BaM/LSMO bilayers. (April 2022) - Zinzuvadiya, Sushant; Pandya, Nirav C.; Sengunthar, Poornima; Pandya, Rutvi J.; Khan, Saif A.; Tripathi, Ambuj; Joshi, U.S.
Abstract: In the present study, we report the structural and electrical properties of pulsed laser deposited (PLD) bilayers of BaFe12 O19 (BaM) and La0.67 Sr0.33 MnO3 (LSMO) thin films deposited on platinized silica substrate. Structural and electrical variation arising due to irradiation of 120 MeV Au +9 ion in these bilayers were studied with different fluences. X-ray diffraction (XRD) shows co-existence of phase pure BaM and LSMO throughout the measurement range. Scanning electron micrographs reveals the influence of irradiation on grains and its density. Frequency dependent real permittivity, imaginary permittivity, tangent loss and AC conductivity are highly affected by irradiation. Well established theoretical models like Maxwell-Wagner polarization, Relaxation mechanism, Universal dielectric response and Jonscher's power law have been employed to explain irradiation induced discrepancies in electrical properties. Magnetic field dependent magnetodielectric properties have been investigated for ion beam assisted modifications in the presently studied samples. Highlights: 120 MeV Au +9 Ion irradiated BaM/Pt and BaM/LSMO ferromagnetic bilayers. Structural, electronic and magnetodielectric properties of irradiated bilayers. Enhanced dielectric effects in irradiated bilayers.